Higher education counseling: Keeping pace with rapidly changing learning environments - Clemeña, Rose Marie Salazar (Animo Repository, 2011)
In a trend report prepared for the 2009 World Conference on Higher Education (WCHE), Altbach et al. (2009) studied the major issues and contextual factors that have influenced higher education worldwide since the 1998 WCHE and proposed possible scenarios for the near future. These include massification of higher education, which poses challenges such as new ways of funding higher education, an overall deterioration of academic standards and a concern for disadvantaged and underserved subgroups; globalization, whose effects are reflected in student mobility (mainly a South-North trend), the widespread use of English as the major language of scientific communication and the concentration of ownership of major resources in strong universities and multinational companies in the developed countries. Other related issues are the inequality among higher education systems worldwide and institutions within countries, due to economic and other disparities; the center vs. periphery dynamic, with large research-intensive universities as centers, and academic institutions that depend on these universities for knowledge and leadership as peripheral. It mustbe noted too, however, that these strong, world-class academic centers tend to give less emphasis on teaching, public service, giving access to underserved groups or other community services. The center/periphery reality is linked with national, regional and global rankings of academic institutions and degree programs that although methodologically flawed, are taken seriously by the public, universities and government policy-makers. Quality, which these rankings stress, is a major concern in postsecondary education. Thus, quality assurance is high on the policy agenda of many governments. Given the other dynamics of globalization and student mobility, the establishment of internationally accepted standards between and among nations becomes a necessity. In this regard, a pattern of peer review and evaluation of institutions against their own self-defined mission is emerging. Increasing importance is also placed on the measurement of learning outcomes, as an essential element in providing greater accountability to the public (Altbach et al. 2009). Such concern for quality has resulted in a global, national and internal competitive environment. Although competition among and within countries as well as within institutions can help achieve excellence, it can also weaken “the sense of an academic community, a mission and traditional values” (Altbach et al. 2009: 15). Prestigious research universities, which provide the most direct link to the global knowledge system, prioritize research over the two other missions of the university-teaching and community service-thus moving teaching and learning from the center to the fringes of academic life. In this competitive environment, questions about students and the curriculum as well as the academic profession become salient. These include the creation of new academic support systems, differentiated curricula, innovative teaching approaches and the strong influence of world-class universities in Englishspeaking countries on the rest of the world because of the primacy of the English language in scientific discourse. On the part of the academics, a general decline in their average academic qualification has been observed, in view of the demands of massification in many countries. Further, the increasingly globalized academic labor market has resulted in academic migration, which continues to be disadvantageous to the developing countries (Altbach et al. 2009). Information and communications technologies (ICT) have increasingly come to influence higher education institutions. Altbach et al. (2009) note that internet-based higher education faces many risks and challenges, particularly as regards quality assurance. But even as the Internet has changed the way knowledge is transmitted, it has also worsened the gap between the “haves” and the “havenots” because of the huge expenses associated with the provision of ICT. The escalating cost of higher education and the dominance of the private sector have sparked a dynamic debate on higher education as a public good vs. a private good (Bigalke and Neubauer 2009). From the traditional concept of higher education providing benefits both to society and to individuals and thus deserving of state support and funding, postsecondary education is increasingly being considered as a commodity largely of value to individuals. By this logic students andacademic institutions should shoulder a significant part of higher education costs. This trend imposes demands on universities and national systems, especially in developing countries, to find solutions to the financial challenges of the privategood philosophy without sacrificing quality. At the same time, the public-good idea, which underlines the public service function of the university and its traditional social role-including being a center of teaching and research as well as of a society’s intellectual and cultural life-cannot simply be set aside. © 2012 Deane E. Neubauer for selection and editorial material; individual contributors, their contribution.